Impact of Investor Sentiment, Exchange Rates, and Foreign Capital Flow on Jakarta Islamic Index Stock Returns - Rizal Ansari; Tulasmi; Sawitri (Journal of Islamic Economics Lariba, 2022)
This study examines the impact of investor sentiment, changes in exchange rates, and foreign capital flow on the Jakarta Islamic Index's return. This study uses daily data between January 2, 2017, and December 30, 2021. After examining the characteristics of autocorrelation and stationarity, we apply the Difference-Generalized Methods of Moment (D-GMM) model. In short, we do not find the effect of investor sentiment on stock returns in both contemporaneous and lag periods. Meanwhile, significant changes in exchange rates have a negative effect on stock returns on contemporaneous and lags, but foreign portfolio flows on contemporaneous and significant lags positively affect stock returns. Thus, our results have implications for trading strategies, asset pricing, and portfolio management carried out by foreign investors on Islamic stocks in Indonesia.